The Imaginary Pilgrimage: The Narrative of Going Home in the Javanese-Moslems Migrant’ Slametan Ritual in Maluku - Tupan, Jobert; Lattu, Izak Y.M; Therik, Wilson M.A. (FIKRAH, 2022)
Migration is not only the movement of people to settle elsewhere, but also cultural displacement. This study reveals the Moslemss tradition among migrants from Central Java in Waihatu, Maluku. The approach of this research is qualitative with the type of research is netnography. Data collection techniques were carried out through documentation, observation and virtual interviews. The subject of this research is the young generation of Javanese Moslemss who are vulnerable to being contaminated by radicalism and extremism and or the essence of Javanese culture. The results of this study are the village slametan ritual in Wahatu is a manifestation of society and its cultural movement. Even though the culture became vacuum due to the disconnection of local wisdom between generations, and was inundated by obstacles due to the local socio-political situation, the event was then revitalized. After being revitalized, the village slametan ritual emerged with its new nuances related to the narrative of an imaginary pilgrimage that was held through spatial and current deterritorialization without Kejawen dimensions and pluralism. The slametan ritual performed by migrantsMoslemss in the village in Waihatu, Maluku, includes; 1) Pendem wedhus kendit; 2) Kungkum; and 3) Cultural carnival. This celebration is the only narrative of going home and as a spiritual theater for Moslemss immigrants. The younger generation of Moslemss immigrants are expected to be moderate actors in achieving prosperity in the village through increasing economic and social solidarity without Javanese culture and recognizing their social life in Maluku.